Nilai-Nilai Spiritual Dalam Buku Menjadi Manusia, Menjadi Hamba Karya Fahruddin Faiz - Iqbal Musthofa; Ida Afidah; N Sausan M Sholeh (Bandung Conference Series: Islamic Broadcast Communication, 2022)
The development of technology facilitates human life in carrying out their lives. On the other hand, technology has a negative impact on people's behavior. The phenomenon of social media today shows how technology is used unwisely. This study aims to present spiritual values in the book Being Human, Being a Servant. This research uses a qualitative type with content analysis method to reveal spiritual values in the book Being Human, Being a Servant by Fahruddin Faiz. The results of the study show that the spiritual values in the book Being Human, Being a Servant by Fahruddin Faiz are contained in ethical, aesthetic, and divine values contained in the discussion of nature, humor, prayer, marriage, playing games in life, time and servitude. When humans understand these three values, they become spiritual values and make humans aware of the nature of their servanthood, and their position and role as. humans.